40 Years of CSF Toxicity Studies in ALS: What Have We Learnt About ALS Pathophysiology? - Ng Kee Kwong, Koy Chong; Harbham, Pratap K.; Selvaraj, Bhuvaneish T.; Gregory, Jenna M.; Pal, Suvankar; Hardingham, Giles E.; Chandran, Siddharthan; Mehta, Arpan R. (Frontiers in Molecular Neuroscience, 2021)
Based on early evidence of in vitro neurotoxicity following exposure to serum derived from patients with amyotrophic lateral sclerosis (ALS), several studies have attempted to explore whether cerebrospinal fluid (CSF) obtained from ALS patients could possess similar properties. Although initial findings proved inconclusive, it is now increasingly recognised that ALS-CSF may exert toxicity both in vitro and in vivo. Nevertheless, the mechanism underlying CSF-induced neurodegeneration remains unclear. This review aims to summarise the 40-year long history of CSF toxicity studies in ALS, while discussing the various mechanisms that have been proposed, including glutamate excitotoxicity, proteotoxicity and oxidative stress. Furthermore, we consider the potential implications of a toxic CSF circulatory system in the pathophysiology of ALS, and also assess its significance in the context of current ALS research.